Increasing Knowledge about First Aid for Falls in Primary School Children - Rozi, Fahru; Ristivani, Irma; Fahrizah, Ismah; Andry, Andry; Maghfira, Azzahra Bulan; Wahyuningtias, Febriana; Dewi, Nabella Kartika; M.H, M.Adamfian; Yunus, Bertold; Fikri, Ahmad Khoirul (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
Elementary school children are those who are in their growth period. During their growth period, it is not uncommon for them to be very active and explore new things. While exploring, some of them may fall, slip, get scratched and get wounds on their hands, foreheads or feet. The wounds they get are certainly a valuable experience for them, but do children know how to handle them properly when a child gets injured? Education needs to be given to children so that children at least know what steps or methods to take when they get injured. Based on the results of observations made by the author at SD Negeri 013, Suko Mulyo Village, Sepaku. Education regarding handling open wounds has not been provided optimally. Therefore, the author conducted outreach at the elementary school regarding handling open wounds in children so that children and teachers at the school would pay more attention to how to handle open wounds when children experience falls or other things that cause injuries. The method used is observation and an approach through Role Playing Models. Respondents consisted of 18 grade 4 children at SD Negeri 013. The results achieved showed that children knew what tools were and how to handle open wounds as evidenced by recalling that children were able to mention first aid steps for open wounds in the correct order.